1999
DOI: 10.1007/bf02842328
|View full text |Cite
|
Sign up to set email alerts
|

Application of Weibull model for redefined significant wave height distributions

Abstract: It is well accepted that the parent distribution for individual ocean wave heights follows the Weibull model. However this model does not simulate significant wave height which is the average of the highest one-third of some 'n' (n-varies) wave heights in a wave record. It is now proposed to redefine significal]t wave height as average of the highest one-third of a constant number (n-constant, say, n = 100) of consecutive individual wave heights. The Weibull model is suggested for simulating redefined signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In this study, the statistical characteristics of H s were analysed using the methodology of fitting a probability distribution function (PDF) to the wave time series at the control points of the ER coastal belt. Many studies have indicated that the probability distribution used to model longterm distributions of wave heights is well represented by the two-parameter Weibull distribution (Muraleedharan et al, 1993(Muraleedharan et al, , 1998(Muraleedharan et al, , 1999. The PDF of a random variable x with the Weibull distribution (Weibull, 1951) is defined for positive values, x > 0, as…”
Section: Extreme-wave Analysismentioning
confidence: 99%
“…In this study, the statistical characteristics of H s were analysed using the methodology of fitting a probability distribution function (PDF) to the wave time series at the control points of the ER coastal belt. Many studies have indicated that the probability distribution used to model longterm distributions of wave heights is well represented by the two-parameter Weibull distribution (Muraleedharan et al, 1993(Muraleedharan et al, , 1998(Muraleedharan et al, , 1999. The PDF of a random variable x with the Weibull distribution (Weibull, 1951) is defined for positive values, x > 0, as…”
Section: Extreme-wave Analysismentioning
confidence: 99%
“…In this study, the statistical characteristics of H s were analysed using the methodology of fitting a probability distribution function (PDF) to the wave time series at the control points of the ER coastal belt. Many studies have indicated that the probability distribution used to model longterm distributions of wave heights is well represented by the two-parameter Weibull distribution (Muraleedharan et al, 1993(Muraleedharan et al, , 1998(Muraleedharan et al, , 1999. The PDF of a random variable x with the Weibull distribution (Weibull, 1951) is defined for positive values, x > 0, as…”
Section: Extreme-wave Analysismentioning
confidence: 99%